2023
DOI: 10.3390/cancers15215257
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Values of Circulating IL-6 and TGF-β Might Identify Patients with HNSCC Who Do Not Benefit from Nivolumab Treatment

Marco Carlo Merlano,
Matteo Paccagnella,
Nerina Denaro
et al.

Abstract: Background: The immunotherapy of head and neck cancer induces a limited rate of long-term survivors at the cost of treating many patients exposed to toxicity without benefit, regardless of PD-L1 expression. The identification of better biomarkers is warranted. We analyzed a panel of cytokines, chemokines and growth factors, hereinafter all referred to as ‘cytokines’, as potential biomarkers in patients with head and neck cancer treated with nivolumab. Materials and methods: A total of 18 circulating cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, elevated IL-6 values in serum collected prior to nivolumab therapy of HNSCC at patients were correlated with their poor survival [ 12 ]. Also, Tsai et al data revealed that IL-6 overexpression was associated with the increased risk of developing disease failure and poor prognosis for HNSCC [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated IL-6 values in serum collected prior to nivolumab therapy of HNSCC at patients were correlated with their poor survival [ 12 ]. Also, Tsai et al data revealed that IL-6 overexpression was associated with the increased risk of developing disease failure and poor prognosis for HNSCC [ 13 ].…”
Section: Discussionmentioning
confidence: 99%